1996
DOI: 10.7601/mez.47.23_1
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of domestic mites and associated housing conditions in concrete-built apartments in Nagoya, Japan

Abstract: 'i:i`meeEAItZ di msNJk pt ; 7ixs me t5 S fist asEGIeenjetpadi Y ta fi3 []i rk es Tg gtss]<\ee\zzEwttz7#as(+466gttimsmwa*lipteefior6s) (Reti1995 lll 8 fi 28 E iffemzafilr995 Ill 11 E 8 H)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Another investigator reported that air conditioning can reduce mite density if it decreases relative humidity to below 50% (29). On the other hand, a recent Japanese study (30) found that specific mite populations, including Der p, were significantly higher in homes with air conditioning. Japanese urban areas are very humid compared with the USA in summer.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Another investigator reported that air conditioning can reduce mite density if it decreases relative humidity to below 50% (29). On the other hand, a recent Japanese study (30) found that specific mite populations, including Der p, were significantly higher in homes with air conditioning. Japanese urban areas are very humid compared with the USA in summer.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the intensive use of air conditioners is likely to reduce the indoor absolute humidity to the 13 g/m 3 level as opposed to the outdoor level of 21 g/m 3 . However, the relative humidity in a room with air conditioning rapidly increases locally near the wall and floor when the air conditioning stops and outdoor air enters (30), because the relative humidity becomes higher as the temperature decreases due to reduced saturated vapor pressure, thus leading to a favorable local climate for mite proliferation. This study has demonstrated a significantly positive relationship between the intensive use of air conditioning in hot weather and atopic sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…19 On the other hand a Japanese study found that specific mite populations, including Der p, were significantly higher in homes with air conditioning. 20 The intensive use of air conditioners is likely to reduce the indoor absolute humidity in comparison to the outdoor level. However the relative humidity in a room with AC rapidly increases locally near the wall and floor when the air conditioning stops and the outdoor air enters, 20 because the relative humidity becomes higher as the temperature decreases due to reduced saturated vapor pressure, thus leading to a favourable local climate for mite proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…[18] On the other hand, a Japanese study found that specific mite populations were significantly higher in homes with air conditioning. [19] Post-operative fungal infections may be caused by discharge of spores from contaminated air conditioning units. [20] The filters of such units may act as a nidus for the growth of fungi according to the study done in 25 operating theatres in India over 2 years.…”
Section: Discussionmentioning
confidence: 99%